Kepercayaan Orang Rimba Jambi terhadap Betetutuh Sang Mesekin - Japarudin, Japarudin (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2014)
This study focused on Orang Rimba identity in term of their religious live. One of Orang Rimba religious tradition was belive in Betetutuh Sang Mesekin or The Saying from Poor People. The assumption of this research was Betetutuh Sang Mesekin could describe who and how was the livelihood of Orang Rimba in the past, and succeeding being seen that identity changed on today. Nowadays, still found that their identity still mantaining, Orang Rimba still lived in the middle of forest, residence near streaming of the river, obedient and unwavering holds custom, petting beard that corelation with confidence. Meanwhile their identity changed, appeared a new interaction model of Orang Rimba with Orang terang. Orang Rimba tried to get cultivation though up custom conjugate with condition of currently, the tradition of Melangun chaged with a new format. A new of custom also appeared like using modern technology such as handphone and etc.